Power House, University of Washington, approximately 1909 - Nowell, Frank H. (1909)
Later referred to as the Power Plant. Caption on image: F.H. Nowell, Official Fotografer - Alaska-Yukon-Pacific Exposition. Photographer's reference number: X769. Handwritten on verso: Seattle - Alaska-Yukon-Pacific Exposition, 1909 - Buildings. Power Plant. PH Coll 727.536 Built in 1909 for the A.Y.P. Exposition, it was intended to be a permanent power house for the university. Major additions were made in 1922, 1935, 1950, 1960, 1962, 1965, and 1969. The Power House was referred to as the Power Plant after 1957.